The Kyoto Protocol - what next? - Schipper, Lisa (2004)
Explores the outcomes at the 9th Session of the Conference of the Parties to the UN Framework for Climate Change in Milan, Italy, and contemplates the future of the international climate regime. Notes that the largest issues on the agenda included the remaining discussion on afforestation and reforestation under the Clean Development Mechanism; and, UN ECCC Secretariat 's 2004-5 budget.